LAW ENFORCEMENT STRATEGIES IN ADDRESSING CRIMINAL ACTS OF LAND GRABBING - Putri, Cindy Aulia (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2024)
Land grabbing is a severe problem because it is typical for someone or a group to take over or grab other people's land and claim it as their own. If preventive legal action is not immediately taken, this can threaten the community's rights and sustainable development in Indonesia. This journal looks at the criminal law enforcement strategy in combating the crime of land grabbing by referring to Article 385 of the Criminal Code. The research method used in this journal is the normative juridical analysis research method, which, in this case, observes the effect of existing laws and how challenges arise in their application in society. The study results have shown that the legal regulation needs to be considered adequate to answer Indonesia's land-grabbing problem. The verdict in the case of criminal land grabbing cannot be used to execute the disputed land because the criminal verdict is intended to punish the perpetrator of land grabbing. Meanwhile, a separate court, namely the civil court, must be established to restore victims' rights.